Sleep dysregulation in sympathetic-mediated diseases: implications for disease progression - Jose Olivares, Maria; Toledo, Camilo; Ortolani, Domiziana; Ortiz, Fernando C.; Diaz, Hugo S.; Iturriaga, Rodrigo; Del Rio, Rodrigo (My University, 2022)
The autonomic nervous system (ANS) plays an important role in the coordination of several physiological functions including sleep/wake process. Significant changes in ANS activity occur during wake-to-sleep transition maintaining the adequate cardiorespiratory regulation and brain activity. Since sleep is a complex homeostatic function, partly regulated by the ANS, it is not surprising that sleep disruption trigger and/or evidence symptoms of ANS impairment. Indeed, several studies suggest a bidirectional relationship between impaired ANS function (i.e. enhanced sympathetic drive), and the emergence/development of sleep disorders. Furthermore, several epidemiological studies described a strong association between sympathetic-mediated diseases and the development and maintenance of sleep disorders resulting in a vicious cycle with adverse outcomes and increased mortality risk. However, which and how the sleep/wake control and ANS circuitry becomes affected during the progression of ANS-related diseases remains poorly understood. Thus, understanding the physiological mechanisms underpinning sleep/wake-dependent sympathetic modulation could provide insights into diseases involving autonomic dysfunction. The purpose of this review is to explore potential neural mechanisms involved in both the onset/maintenance of sympathetic-mediated diseases (Rett syndrome, congenital central hypoventilation syndrome, obstructive sleep apnoea, type 2 diabetes, obesity, heart failure, hypertension, and neurodegenerative diseases) and their plausible contribution to the generation of sleep disorders in order to review evidence that may serve to establish a causal link between sleep disorders and heightened sympathetic activity.
Keywords: sleep regulation; autonomic nervous system; arousal; sympathetic hyperactivity; sympathetic-mediated diseases